Analisis Nilai-Nilai Pendidikan dalam Budaya Dalihan Na Tolu dan Relevansinya bagi Siswa SDN 159 Purba Baru - Aida, Nur; Aini, Nur; Hariyanti, Melpa; Adelina, Rika Fitri; Anisa, Sangkot; Wahyuni, Rahmi (Jurnal Pendidikan Dirgantara, 2025)
This study aims to analyze the educational values contained in the Dalihan Na Tolu culture in the Mandailing community and its relevance to character education in schools. The research approach used is qualitative descriptive with data collection techniques through interviews, observations, and documentation of traditional leaders and the Mandailing community in Mandailing Natal Regency. The results of the study show that Dalihan Na Tolu, which includes the principles of Somba Marhula-hula, Elek Marboru, and Manat Mardongan Tubu, contains educational values such as respect, responsibility, empathy, cooperation, and mutual cooperation. These values have a strong relevance to character education in elementary school. The culture of Dalihan Na Tolu not only serves as a social system, but also as a source of moral and character education for the younger generation. In addition, the application of these traditional values in the context of modern education can strengthen students' cultural identities and foster mutual respect in the school environment. The integration of Dalihan Na Tolu into learning also has the potential to be an effective pedagogical strategy to build a harmonious and characterful school culture.